Abundance of phytoplankton in the Levantine Basin during the Bilim 2 cruise in April 2008 - Zahit Uysal (PANGAEA, 2015)
The dataset is composed of 44 samples from 11 stations. The phytoplankton samples were collected by 5l Niskin bottles attached to the CTD system. The sampling depths were selected according to the CTD profiles and the in situ fluorometer readings. The samples (50 ml sea water) were preserved with prefiltered (0.2 micron) glutardialdehyde solution (1.5 ml of commercial glutardialdehyde (25%)) into dark colored glass bottles. Preserved samples were poured into 10 or 25 ml settling chambers (Hydro-Bios) for cells to settle on the bottom over a day. Species identification and enumeration were done under an inverted microscope (Olympus IX71). At least 400 specimen were tried to be counted in each sample.